Kajian Penerapan GCG, Kinerja Keuangan dan Kaitannya dengan Nilai Perusahaan Yang Terdaftar di LQ-45 - Santoso, Hadi (MABIS, 2011)
This study examines the influence of good corporate governance mechanisms consisting of the number of independent Commisioner members, institutional ownership, the number of audit committee members, the number of board members, return on assets and the price to book value ratio of the selected companies. This study uses as its sample, the 36 companies listed in the LQ-45 from the period August 2008 until January 2010. The data used are taken from the annual reports of the companies from 2008 to 2010. Data are analyzed with classical assumption test and multiple linear regression analysis using SPSS version 16. The normality test shows a normal distribution of data in this study; there is no multicollinearity or heteroscedasticity, and no autocorrelation. Hypothesis testing shows variable X1 (number of independent commisioner members), variable X2 (Institutional Ownership), and variable X3 (number of audit committee) had no significant effect on firm value. However, variable X4 (number of board members) and variable X5 (return on assets) show significant effect on firm value. Simultaneous testing demonstrated a significant effect from the five independent variables on firm value. The analysis indicates that applied good corporate governance will significantly affect company performance and hence will be transferred to company